A POSTCRANIAL SKELETON OF THE GORGONOPIAN VIATKOGORGON IVACHNENKOI (REPTILIA, THERIODONTIA) FROM THE UPPER PERMIAN KOTELNICH LOCALITY, KIROV REGION - Tatarinov L.P. (My University, 2004)
Viatkogorgon ivachnenkoi Tatarinov is a small gorgonopian with well-developed gastralia and hypapophyses of the caudal vertebrae and broad and short feet with distal intertarsal contacts. This animal was apparently a relatively good swimmer. The gastralia of Viatkogorgon were acquired secondarily (punctuated homology).
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская